2004
DOI: 10.1023/b:pham.0000041450.25106.c8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biowaivers Among Class II Drugs: Theoretical Justification and Practical Examples

Abstract: The underlying reason for a region of fully absorbed drugs in Class II originates from the dynamic character of the dissolution-uptake processes. The dynamic character of the approach developed allows identification of biowaivers among Class II drugs. Several biowaivers among the NSAIDs were identified using solubility data at pH 5.0 and in fed-state-simulated intestinal fluid at pH 5.0. The relationships of formulation parameters, dose, particle radius, and the drug properties, dimensionless solubility/dose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 14 publications
0
43
0
4
Order By: Relevance
“…According to Table 4, P app (AP→BL) was less than 2×10 -6 cm/s [32] due to the effl ux (P-gp, MRPs) function and high hydrophilicity paired with low lipid solubility, indicating that FTA might belonged to the class III of the biopharmaceutical classification system (BCS) [33] . The permeation through biomembranes is a rate-limiting process that results in low oral BA.…”
Section: Discussionmentioning
confidence: 99%
“…According to Table 4, P app (AP→BL) was less than 2×10 -6 cm/s [32] due to the effl ux (P-gp, MRPs) function and high hydrophilicity paired with low lipid solubility, indicating that FTA might belonged to the class III of the biopharmaceutical classification system (BCS) [33] . The permeation through biomembranes is a rate-limiting process that results in low oral BA.…”
Section: Discussionmentioning
confidence: 99%
“…Yazdanian and collaborators (2004) investigated NSAID (non-steroidal anti-inflammatory drug) in a study and showed an increased drug solubility when FeSSIF and FaSSIF instead of buffers 0.1 N HCl (pH 1.2), 0.02 M citric acid (pH 5.0) and 0.02 M Na 2 HPO 4 , and 0.02 M NaH 2 PO4 (pH 7.4) were used (90). Rinaki et al developed a dynamic GI absorption model and showed that such solubility data generated in biorelevant media can be used as guidance for the formulation scientist in the development phase (92).…”
Section: Biorelevant Mediamentioning
confidence: 99%
“…Over the past 25 years, mathematical models have been developed to estimate in vivo drug absorption from in vitro drug concentration-time data (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). These biopharmaceutical models base their prediction of drug absorption on physicochemical properties of the drug (solubility, pKa, physical state), physiological properties (absorption rate constant, local pH, transit time), and dosage form (17).…”
Section: Introductionmentioning
confidence: 99%